Language and folklore of Tukhalars of Mongolia - Nadezhda D. Suvandii, Elena M. Kuular, Ailanmaa M. Soyan, (Opción, 2019)
The purpose is the description of the live speech and folklore of small ethnic groups of Tukhalars of the Sumon of Tsagaan-Nuur. The main methods are the method of a field research, descriptive, comparative-historical, and comparative and linguostatistics ones. Results of research demonstrate that language and folklore of Tuvinians of Mongolia keep so far a number of archaic elements in which there are similarities to maternal tradition. As a conclusion, at small genres of folklore there are original proverbs and sayings which characterize their traditional moral values.